Cyberloafing: A preliminary study from Indonesian workers - Hendryadi, Hendryadi; Mustika, Maya (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
The primary objective of this study was to create a comprehensive measurement scale for cyberloafing from the perspective of Generation Z in Indonesia. The research was conducted in two stages. The first stage involved 145 participants for initial validity, and the second stage included 214 respondents for the final validation. Two distinct factors were identified through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA): personal interest and social cyberloafing. These factors comprised 11 items, providing a more in-depth understanding of cyberloafing and its prevalence in Gen Z populations. The article also discussed the study's limitations and provided recommendations for future research.